Outcome of emergency patients transported by ambulance during the COVID-19 pandemic in Osaka Prefecture, Japan: a population-based descriptive study - Katayama, Yusuke; Tanaka, Kenta; Domi, Hisaya; Masui, Jun; Nakao, Shunichiro; Tachino, Jotaro; Hirose, Tomoya; Kitamura, Tetsuhisa; Oda, Jun; Matsuoka, Tetsuya (Frontiers in Public Health, 2024)
Background The novel corona virus (COVID-19) pandemic occurred worldwide. Although an excessive burden was placed on emergency medical institutions treating urgent and severe patients, its impact on patient outcome remains unknown. This study aimed to assess the impact of the COVID-19 pandemic in 2021 on the emergency medical services (EMS) system and patient outcomes in Osaka Prefecture, Japan. Methods This was a retrospective descriptive study with a study period from January 1, 2019 to December 31, 2021. We included patients who were transported by ambulance and had cleaned data that was recorded in the ORION system. The study endpoints were the number of patients transported by ambulance and the number of deaths among these patients in each month. To assess the impact of the COVID-19 pandemic on the EMS system, the incidence rate ratio (IRR) and 95% confidence interval (CI) were calculated using 2019 as the reference year. Mortalities were evaluated based on deaths in the emergency department and deaths at 21 days after hospitalization. Results The numbers of patients transported by ambulance were 500,194 in 2019, 443,321 in 2020 (IRR: 0.88, 95% CI: 0.87–0.88), and 448,054 in 2021 (IRR: 0.90, 95% CI: 0.89–0.90). In 2019, the number of patients transported by ambulance and who died in the emergency departments was 4,980, compared to 5,485 in 2020 (IRR: 1.10, 95% CI; 1.06–1.44) and 5,925 in 2021 (IRR: 1.19, 95% CI: 1.15–1.24). In 2019, the number of patients who died within 21 days after hospitalization was 11,931, compared to 11,913 in 2020 (IRR; 1.00, 95% CI; 0.98–1.03) and 13,376 in 2021 (IRR; 1.12, 95% CI; 1.09–1.15). Conclusion The COVID-19 pandemic decreased the number of ambulance requests and worsened mortality of patients transported by ambulance in Osaka Prefecture during 2021.